Incidence of resistant microorganisms after COVID-19 respiratory syndrome: An integrative review (Research, Society and Development, 2022)
This study aimed to analyze the incidence of bacterial resistance after COVID-19 infection. To carry out this integrative literature review, the study base was: Incidence of bacterial resistance after COVID infection. A survey of articles in the literature for this review was carried out in the following databases: LILACS, BVS (virtual health library), PubMed and Scielo. The following keywords and their combinations in Portuguese and English were used to search for articles: “COVID-19”, “bacterial resistance” and “coinfection”. All words were previously consulted in the Health Sciences Descriptors (Decs). The survey took place between April and June 2022. The predisposition to the development of bacteria and fungi is being evident in patients who contracted the coronavirus. COVID-19 patients have reported dimensions of complications, including respiratory distress syndrome, case fatality rates or other variables associated with these complications. Among the post-COVID-19 respiratory syndrome diseases, case studies of mitral valve prosthetic infective endocarditis, native valve infective endocarditis, bilateral endophthalmitis, mitral-aortic infective endocarditis complicated by heart failure and hemorrhagic stroke, mucormycoses, inflammatory syndrome were found. pediatric multisystem disease and lymphocytopenia in patients with thalassemia. These are recent reports, and further studies are still needed to correlate the extent of the severity of the influence of COVID-19 with bacterial resistance. We conclude that co-infections with various microorganisms are commonly found in patients infected with SARS-CoV-2 that significantly influence the severity and mortality rates of COVID-19.